PENGARUH KOMPETENSI, MOTIVASI KERJA DAN INSENTIF TERHADAP KINERJA GURU SMA - Helen Purnama Sari (Perspektif Ilmu Pendidikan, 2019)
This research aims to (1) know the influence of teacher’s competence, work motivation, and incentive on teacher’s performance at once, (2) know the influence of teacher’s competence on teachers’ performance, (3) know the influence of work motivation on teachers’ performance, (4) know the influence of incentive on teachers’ performance. This research method used in this study is quantitative research using survey. The population of the study was 127 teachers of two senior high schools and the sample was 96 teachers. The simple random sampling was applied to choose the sample for this study. The questionnaires were the instruments used in collecting data of teacher’s competence, work motivation, and incentive while the observation sheet was the instruments used in collecting data of teacher’s’ performance. The results of prerequisite test were normally distributed, linier, homogenous, do not occur multi co-linearity and neither does autocorrelation. The data was analyzed using multiple linier regression with significance level 0,05. This research reveals that (1) there is a positive significance of influence among competence, teacher’s work motivation, and incentive on teachers’ performance at once; (2) there is a positive significance of influence between competence on teachers’ performance; (3) there is a positive significance of influence between motivation of teacher work on teachers’ performance; (4) there is a positive significance of influence between incentive on teachers’ performance.